2003
DOI: 10.1309/5h778w5k75cmm03w
|View full text |Cite
|
Sign up to set email alerts
|

Her-2/neuGene Amplification in Familial vs Sporadic Breast Cancer

Abstract: We compared the incidence of Her-2/neu amplification in patients with and without a family history of breast cancer and correlated gene status with clinicobiologic and prognostic features in sporadic and familial cases. Of 108 patients, 28.7% had gene amplification. Among 96 cases with family history information available, 28 had an affected first-degree relative. The gene was amplified more frequently in familial than in sporadic cases (13/28 [46%] vs 14/68 [21%]; P = .01). Among familial cases, amplification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…30 It is not clear why p53 mutations are associated with Her-2 gene amplification. 39,40 Ki-67 is a nuclear protein that is commonly used for the detection and quantification of proliferating cells. 28 In agreement with the observations by others, 35,50,51 it was found that Ki-67 positively connected with Her-2 overexpression in this study, suggesting that Her-2 overexpression might upregulate the expression of Ki-67.…”
Section: Discussionmentioning
confidence: 99%
“…30 It is not clear why p53 mutations are associated with Her-2 gene amplification. 39,40 Ki-67 is a nuclear protein that is commonly used for the detection and quantification of proliferating cells. 28 In agreement with the observations by others, 35,50,51 it was found that Ki-67 positively connected with Her-2 overexpression in this study, suggesting that Her-2 overexpression might upregulate the expression of Ki-67.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that patients with HER2 -amplification in breast cancer tissue showed shorter disease-free time intervals and they benefit from therapy with the anti-Her-2/neu antibody, Herceptin [6,19,25]. …”
Section: Introductionmentioning
confidence: 99%